Whole-Genome Analysis of an Extensive Drug-Resistant Acinetobacter Baumannii ST195 Isolate from a Recipient After DCD Renal Transplantation in China - Hong Jiang; Luxi Cao; Qixia Shen; Lihui Qu; Yan Jiang; Tingting Qu; Jian Zhang; Yingying Lu; Bingjue Li; Chaohong Zhu; Guangjun Liu; Rending Wang; et al. (Karger Publishers, 2017)
Background/Aims: Infection with Acinetobacter baumannii was emerging as one of the leading causes of mortality after donation after cardiac death transpalantion. Methods: We reported a case of a recipient who underwent DCD renal transplantation and later got infected by A.baumannii. Etests were done to verify the susceptibility test results in clinic. Whole-genome analysis was applied to investigate the resistant mechanism at gene level. Results: The pathogen was isolated from his draining liquid the day after the surgery, and susceptibility test reavealed that it was sensitive to tigecycline. However, the isolate obtained from the draining liquid became tigecycline-resistant after fifteen-day administration of tigecycline. The Susceptibility tests showed that the pathogen recovered from tigecycline resistance and became intermediated to tigecycline. Whole-Genome analysis revealed the genetic level change leading to tigecycline resistance and we identified the location of mutation by comparing the whole genome sequence of the isolates. Three loci were figured out which may contribute to drug resistance, including genes encoding HTH domain protein, MFS transporter and AdeS. Conclusion: Understanding the genetic characteristics associated with drug resistance mechanism and antimicrobial profiles of pathogen is important in controlling infection outbreak and preventing serious complications and gives a new insight into the development of antimicrobial agents.